أثر رأس المال الفكري على إدارة الجودة الشاملة" دراسة ميدانية: على الشركات الصناعية الدوائية وغير الدوائية المساهمة العامة المدرجة في سوق عمان المالي - ارشيد الصرايرة, شادي; يوسف النجداوي, أكرم (Recherches économiques et managériales; Vol. 12 (2012): RECHERCHES ÉCONOMIQUES ET MANAGÉRIALES (DÉCEMBRE))
A Field Study :on Industrial pharmaceutical companies and none-drug public shareholding listed at Amman Financial Market This Study aimed to identify the impact of intellectual capital on total quality management . And it is a field study on Industrial pharmaceutical companies and none-drug public shareholding listed at Amman Financial Market , with number of (80) companies . And towards that goal a questionnaire had been designed which was distributed on the ( 20 ) companies of the study sample , so out of ( 140 )  distributed  questionnaires a number of  (133 ) were retrieved and only about ( 120 )  questionnaire were good for statistical analysis    One of the main results of this study , that the intellectual capital was to be considered one of the  most important intangible assets that contributes significantly in gaining the Organization's income , and there were an effect of it's components ( human capital , structural capital , and customer capital ) on the total quality management of the industrial pharmaceutical companies and none-drug , also showed a significant  effect for the human capital and noticeably on  managing total quality of the above mentioned companies, and with  the existence of significant effect for structural capital  on  managing total quality for the same industrial  companies . However, this effect was not significant when studying the the effect of the intellectual capital components, and this shows that the concern of structural capital in applying the total quality management is less concern  than of the two other kinds .    Also the results showed the existence of significant effect for the customer  capital on the total quality management of the industrial and  pharmaceutical   and none-drug companies , when studying this effect individually , but the effect of the customer capital was not significant when studying the effect of the whole components of intellectual capital in the companies of pharmaceutical industry but with the significant  existence in the non-drug industrial companies . The study included a group of recommendations, one of the most important issues are the necessity of achieving more concern of the development  of    intangible assts by their managers . And setting the programs and policies    which can support developing individuals and increasing the efficiency of it's staff and improving their ability to solve issues in a modern creative and innovative. And the concern of studying market's needs and the changes of  the customers needs .And applying any technological innovative changes  which affects on the changes of customers needs. And the necessity of establishing information system aims to facilitate the operation with the Clients relations managing  (CRM) to followed their needs and measuring the level of saturation and preserving loyalty and getting the competitive advantage in the market . الملخص      استهدفت هذه الدراسة التعرف على أثر رأس المال الفكري على إدارة الجودة الشاملة. وهي دراسة ميدانية على الشركات الصناعية والدوائية المدرجة في سوق عمان المالي، والبالغ عددها (80) شركة. وباتجاه ذلك الهدف تم تصميم إستبانة، وزعت على عينة الدراسة البالغة (20) شركة. حيث تم توزيع (140) إستبانة أسترد منها (133) إستبانة الصالح منها للتحليل الإحصائي (120) استبانة.     ومن أهم النتائج التي توصلت الدراسة إليها: ان رأس المال الفكري يعتبر من أهم الأصول غير الملموسة التي تساهم بشكل كبير في توليد إيرادات المنظمة، وبانه يوجد تأثير لمكوناته (رأس المال البشري، ورأس المال الهيكلي ورأس المال الزبوني) على إدارة الجودة الشاملة في الشركات الصناعية الدوائية وغير الدوائية، كما تبين وجود تأثير معنوي لرأس المال البشري وبشكل ملحوظ على إدارة الجودة الشاملة في الشركات الصناعية الدوائية وغير الدوائية، وبانه يوجود تأثير معنوي لرأس المال الهيكلي على إدارة الجودة الشاملة في الشركات الصناعية الدوائية وغير الدوائية. إلا أن هذا التأثير لم يكن معنوياً عند دراسة تأثير مكونات رأس المال الفكري، وهذا يوضح أن الاهتمام برأس المال الهيكلي في تطبيق إدارة الجودة الشاملة هو أقل من الاهتمام بالنوعين الآخريين. كما وأظهرت النتائج وجود تأثير معنوي لرأس المال الزبوني على إدارة الجودة الشاملة في الشركات الصناعية الدوائية وغير الدوائية، وذلك عند دراسة هذا التأثير بشكل منفرد، إلا أن تأثير رأس المال الزبوني لم يكن معنوياً عند دراسة تأثير مكونات رأس المال الفكري مجتمعة وذلك في شركات الصناعة الدوائية، مع بقاءه معنوياً في الشركات الصناعية غير الدوائية. وقد تضمنت الدراسة مجموعة من التوصيات، من أهمها ضرورة قيام ادارة الشركات بالاهتمام بتنمية أصولها غير الملموسة. ووضع البرامج والسياسات التي من شأنها تطوير الأفراد وزيادة كفاء العاملين وقدرتهم على حل المشاكل بطرق حديثة مبتكرة وابداعية. وضرورة الاهتمام بدراسة السوق والتغير في حاجات الزبائن. وتتبع المتغيرات في التكنولوجيا التي تنعكس على التغير في حاجات الزبائن. وبضرورة العمل على انشاء نظم معلومات تهدف إلى تسهيل عملية إدارة العلاقات مع العملاء (CRM) لتتبع حاجات العملاء وقياس مستوى الاشباع وحفظ الولاء والحصول على الميزة التنافسية في السوق. -